2014
DOI: 10.1186/1754-6834-7-95
|View full text |Cite
|
Sign up to set email alerts
|

Ensiling and hydrothermal pretreatment of grass: consequences for enzymatic biomass conversion and total monosaccharide yields

Abstract: BackgroundEnsiling may act as a pretreatment of fresh grass biomass and increase the enzymatic conversion of structural carbohydrates to fermentable sugars. However, ensiling does not provide sufficient severity to be a standalone pretreatment method. Here, ensiling of grass is combined with hydrothermal treatment (HTT) with the aim of improving the enzymatic biomass convertibility and decrease the required temperature of the HTT.ResultsGrass silage (Festulolium Hykor) was hydrothermally treated at temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…While ensiling of WS in combination with HTT facilitated a reduction in HTT temperature up to 20 °C, ensiling of SCB consistently increased HTT efficiency in terms of cellulose digestibility in 10–15%. The impact of structural differences of biomass has been further confirmed when similar experiments were performed on grass [13]. Even though the ensiling of grass prior HTT caused also increased solubilization and higher concentration of cellulose in the solid fibers compared to non-ensiled grass, the improvement was significantly lower than that found on WS and now on SCB.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…While ensiling of WS in combination with HTT facilitated a reduction in HTT temperature up to 20 °C, ensiling of SCB consistently increased HTT efficiency in terms of cellulose digestibility in 10–15%. The impact of structural differences of biomass has been further confirmed when similar experiments were performed on grass [13]. Even though the ensiling of grass prior HTT caused also increased solubilization and higher concentration of cellulose in the solid fibers compared to non-ensiled grass, the improvement was significantly lower than that found on WS and now on SCB.…”
Section: Resultsmentioning
confidence: 77%
“…However, ensiling of wheat straw prior to HTT has shown significant improvement of pretreatment and overall 2G bioethanol process, being proposed to reduce pretreatment costs on large-scale operations by reducing the HTT temperature or by increasing overall conversion yields [12]. Similar experiments on grass have shown that the improvements are significantly lower than on wheat straw, which emphasizes that the effect of ensiling in HTT is biomass dependent [13].…”
Section: Introductionmentioning
confidence: 99%
“…4,9,21-23 Indeed, even though it is only a few years since their discovery LPMOs are already included in commercial enzyme preparations, from which advances in bioethanol production have been driven. 24,25 Given the fundamental nature of LPMO biochemistry and the major industrial applications of polysaccharide-degrading enzymes, a question is now posed as to the full range of potential substrates upon which LPMOs might act, especially starch, which is the most abundant storage glucan in plants and a polysaccharide of industrial importance. 26 Such is the significance of starch-containing crops that their production is greater than for all other industrial or food substrates combined.…”
Section: Introductionmentioning
confidence: 99%
“…The glucose yield was presented per DM fibre in the hydrolysis and calculated as described by Ambyejensen et al . (2014). Cellulose convertibility was calculated using Equation Cellulose convertibility=false(GY·0.9false)false/cellulose content…”
Section: Methodsmentioning
confidence: 99%
“…The supernatants were used for glucose analysis following the procedures of Desta et al (2016). The glucose yield was presented per DM fibre in the hydrolysis and calculated as described by Ambyejensen et al (2014). Cellulose convertibility was calculated using Equation 1Cellulose convertibility ¼ ðGY Á 0:9Þ=cellulose content (1) Statistical analysis SAS 8.0 software (SAS Inst.…”
Section: Enzymatic Hydrolysismentioning
confidence: 99%